2013
DOI: 10.1128/aac.01232-12
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase 2 Trial To Evaluate the Clinical Efficacy of Two High-Dosage Tigecycline Regimens versus Imipenem-Cilastatin for Treatment of Hospital-Acquired Pneumonia

Abstract: cIn a previous phase 3 study, the cure rates that occurred in patients with hospital-acquired pneumonia treated with tigecycline at the approved dose were lower than those seen with patients treated with imipenem and cilastatin (imipenem/cilastatin). We hypothesized that a higher dose of tigecycline is necessary in patients with hospital-acquired pneumonia. This phase 2 study compared the safety and efficacy of two higher doses of tigecycline with imipenem/cilastatin in subjects with hospital-acquired pneumoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
182
3
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(199 citation statements)
references
References 22 publications
8
182
3
6
Order By: Relevance
“…A recent phase 2 study in HAP and VAP investigated the use of two high-dosage (HD) tigecycline regimens (200 mg initial, and then 100 mg twice daily or 150 mg initial and then 75 mg twice daily) showing higher cure rates when the ''highest'' HD was used compared to lower dosage and imipenem/cilastatin [16]. The study hypothesized that a higher area under the concentration-time divided by the MIC (AUC/ MIC ratio) above one was necessary on the basis of a previous phase 3 study demonstrating lower cure rates in patients with HAP treated with conventional dose of tigecycline; this effect was attributed to a lower exposure to the drug on the lung tissue level [16]. This undermines the necessity of high doses when the MIC of the pathogen exceeds 0.5 mg/L.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A recent phase 2 study in HAP and VAP investigated the use of two high-dosage (HD) tigecycline regimens (200 mg initial, and then 100 mg twice daily or 150 mg initial and then 75 mg twice daily) showing higher cure rates when the ''highest'' HD was used compared to lower dosage and imipenem/cilastatin [16]. The study hypothesized that a higher area under the concentration-time divided by the MIC (AUC/ MIC ratio) above one was necessary on the basis of a previous phase 3 study demonstrating lower cure rates in patients with HAP treated with conventional dose of tigecycline; this effect was attributed to a lower exposure to the drug on the lung tissue level [16]. This undermines the necessity of high doses when the MIC of the pathogen exceeds 0.5 mg/L.…”
mentioning
confidence: 99%
“…Furthermore, compared to colistin that did not reach sufficient drug levels in the lung tissue, HD tigecycline was efficacious for treating experimental pneumonia due to metallo-beta-lactamase (NDM-1)-producing Enterobacteriaceae [17]. Although no major issues of toxicity have been displayed at high doses so far, the tolerability of these regimens in large trials still needs to be assessed [16]. Finally, tigecycline's propensity to select for resistant strains (e.g., MDR Acinetobacter spp.)…”
mentioning
confidence: 99%
“…Ramirez et al compared a higher dose regimen of Tigecycline in a phase two trial for HAP/VAP showing higher clinical efficacy for the higher dose group. 11 But since adequate numbers of patients were not enrolled, the results could not be statistically analysed to be significant. Furthermore, Acinetobacter was not an etiologic agent in the patient group.…”
Section: Discussionmentioning
confidence: 99%
“…This is a reassuringly high rate in the light of data obtained in the phase III HAP study of tigecycline versus imipenem that failed to confirm the non-inferiority of tigecycline in the clinically evaluable patient subset. A subsequent phase II study with tigecycline used at higher dosages indicated increased efficacy with a clinical cure rate of 85 % [16]. There are several, at least, theoretical reasons why non-bactericidal antimicrobial agents such as tigecycline are effective in severe infections [17].…”
Section: Discussionmentioning
confidence: 99%